The Orion Center bibliography of the Dead Sea scrolls and associated literature (2000-2006) - Clements, Ruth. (Studies on the texts of the Desert of Judah,, 2007)
The Orion Center Bibliography of the Dead Sea Scrolls and Associated Literature (2000-2006) is the fifth official Scrolls bibliography, following volumes covering the periods 1948-1957 (W. S. LaSor), 1958-1969 (B. Jongeling), 1970-1995 (F. García Martínez and D. W. Parry), and 1995-2000 (A. Pinnick). The interdisciplinary cast of the Bibliography reflects the current emphasis in Scrolls scholarship on integrating the knowledge gained from the Qumran corpus into the larger picture of Second Temple Judaism. The volume contains over 4100 entries, including approximately 850 reviews; source, subject, and language indices facilitate its use by scholars and students within and outside the field. This work is based on the On-Line Bibliography maintained by the Orion Center for the Study of the Dead Sea Scrolls, Jerusalem.